Unspoken Challenges: Maternal Complexities in Three Asian Short Stories - Derianty, Anna Patrisia (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
This study examines the unspoken challenges experienced by Asian mothers through the lens of Asian motherhood as depicted in literature. The research aims to investigate how cultural norms and societal expectations shape the roles and experiences of mothers in Asian societies. Employing qualitative research methods, specifically thematic analysis, this study interprets and classifies the unspoken challenges portrayed in three short stories from Indonesia, China, and Japan. The findings reveal three prominent themes: developing resilience, performing silent sacrifice, and facing individual conflicts. The mothers in these stories exhibit diverse coping strategies in response to the unacknowledged challenges they encounter. This study contributes to the understanding of the enduring nature of traditional gender roles and expectations in Asian societies, highlighting the need for greater recognition and support for mothers facing these unspoken challenges. The results underscore the importance of continued research and dialogue on the experiences of Asian mothers to promote gender equality and the well-being of women in these contexts. The insights gained from this study can inform future research, policy, and practice aimed at addressing the unspoken challenges faced by mothers in Asian societies and beyond.